Foster student's science literacy skills on environmental pollution topics through the etnoscience approach - Wardah Nabilah; Elok Sudibyo; Ernita Vika Aulia (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram, 2022)
This study aims to describe the improvement of students' science literacy on environmental pollution topics using an ethnoscience approach. The type of research is pre-experimental with a pretest-posttest one-group design. This research was conducted on students of class VII-B of State junior high school (SMP Negeri 49 Surabaya, Indonesia) in the 2021/2022 school year. Research instruments used are pretest-posttest sheets and response questionnaires. Data collection techniques used in this study include tests and questionnaires. The data analysis techniques used are normality tests, t-paired tests, and N-Gain tests. The results showed that students' science literacy increased significantly after applying ethnoscience-based learning to environmental pollution topics. The t-pair test obtained a p-value = 0.000 < 0.05, which significantly differed between post-test and pretest scores. N-Gain also gained an average of 0.73, which shows an increase in the science literacy ability of students with high categories. The results of student responses to learning with an ethnoscience approach to practicing student science literacy fall into the category of excellent, with an overall percentage of 97.5%. This study concludes that students' science literacy has improved after learning an ethnoscience approach to environmental pollution topics.